The Jewish ethic and the spirit of socialism - Weisberger, Adam M. (Studies in German Jewish history, 1997)
The Jewish Ethic and the Spirit of Socialism is an investigation into the appeal of socialist politics to alienated bourgeois German Jews during the Wilhelmine period, 1871-1918. Its central argument is that two conditions attracted German Jews to socialism: a structural marginality resulting from resurgent German anti-Semitism, and secular Jewish messianism